Pemanfaatan Aplikasi Kahoot dalam Pembelajaran Membaca Pemahaman Teks Numerik - R. Mekar Ismayani (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study aims to examine the effect of the use of the Kahoot application in teaching materials for reading numerical texts on students' understanding and ability to solve problems related to the material. The research design used was an experiment with a quantitative approach, with a pre-test post-test control group model. The research sample consisted of two classes of junior high school grade VII students, each of which was given different treatment, namely the use of the Kahoot application in the experimental group and the conventional method in the control group. The results showed that the use of the Kahoot app could improve students' understanding of social arithmetic material, with a significant increase in scores in the experimental group (25 points) compared to the control group (8 points). In addition, the Kahoot application has also been shown to increase student motivation and participation in learning, with the majority of students feeling more interested and motivated to learn actively and collaboratively. These findings suggest that the use of the Kahoot app can be an effective tool for improving learning outcomes and student engagement in math learning.